Kreativitas Imajinasi: Rihlah Mempertemukan Mainstream Psikoanalitik dan Psiko-Sufistik - Hariansyah Hariansyah (Khatulistiwa, 2016)
Initiated by the hypothesis of Ahmad 'Izzat rajih that thinking is a conscious activity with originality as its destination. Meanwhile, through the theory of Oedipus complex, Freud opened the debate that the discourse on creativity must include the discourse on God. Freud's courageous act immediately leaves a serious issue. Serious impact can be seen from the history of thought in the West as if flowing in a flat mannet, without criticism and with the same pattern of implication. These viruses then infected the thought in the Islamic world even more acute in the modern period even though it had previously orbited creative thinkers with a diverse spectrum of original ideas to break away from the acute disease of original ideas such as al-Ghazali, Ibn 'Arabi, Mulla Sadra until Suh}rawardi al- Maqtul. This paper, through academic journey which initiates a meeting point for psychoanalytic-sufic approach, reveals that the original reason for the implementation of creative imagination is a purified fundamental psychological function.